Impact of suplementation vitamins d, c and k on osteoporosis - Igor Staszewski; Gracjan Różański; Anna Maria Dobosiewicz; Nataliia Badiuk (Kazimierz Wielki University, 2018)
Osteoporosis is a skeleton disease characterized by a decrease in bone mass, disturbance of their microarchitecture and reduction of bone mineral density (BMD). Decreased bone quality is manifested by a higher risk of fractures, but bone pain and lowering of growth may occur earlier, although osteoporosis may occur asymptomatically before the fracture occurs. It is a disease of older people, affects 25 to 30% of postmenopausal women, while morbidity among men over 50 is around 8%. Bone tissue is subject to continuous remodeling as a result of resorption processes (release of minerals from the tissue) regulated by osteoclast activity and bone matrix construction by absorption of mineral components to maintain quality and bone mass resistance. In this study attention will be focused on the impact of vitamin supplementation on the development of osteoporosis